An investigation into the impact of funding on operational performance - Kufahakurotwe, Ropafadzo (Midlands State University, 2014)
A number of concepts revolve around excellent operations in the going concern of organizations. The concept of adequate capital to fund operations depends on the obtainable funds available to an entity is one vital concept for effective and efficient operations. Jameson. K (2009) brings out an argument that it is capital that provides businesses the ability to progress as well as maintain a competitive advantage. The need for funds makes progress a virtue in the day to day operations. Funds are generated either internally (profits) or externally that is borrowing privately form banks or through stock issue. The aim of the study of this research is to bring out the effect in lack of funding on operations resulting in poor financial performance. Conclusions gathered as support of the thesis was obtained through findings and experience. Literature review was on the acknowledgement of other scholar’s researches to bring out the net concept of funding. On presentation and analysis of data the researcher used graphs and charts the use of the mode mean and standard deviation was used on data analysis. The results showed that there is every need for a clear funding policy in organizations; funds for Sable are needed to fund the production system and working capital. The company needs to review internal funding by increasing sales which is attained through increased share market and increased volumes. Considerations should be taken on the implementation of long term borrowing as a source of funding.